Capture carbon, capture value: An overview of CCS business models - Bassam Fattouh; Hasan Muslemani; Raeid Jewad (The Oxford Institute for Energy Studies, 2024)
Carbon capture, and storage (CCS) is identified as a critical technology to reduce CO2 emissions to achieve global climate goals. The potential of CCS as mitigation technology could be substantial yet deployment levels remain far below what is needed to make meaningful climate contributions. This paper identifies main commercial and non-commercial risks associated with CCS and analyse incentive mechanisms, regulatory and legal frameworks, types of industry and ownership structures, and public-private partnerships that are likely to emerge in different parts of the world to mitigate these risks and enable viable business models to scale up the technology.
Keywords: 330; Carbon Capture and Storage; CCS; Climate Action; decarbonization; net-zero